DISCOURSE ANALYSIS ON CIVIL CONFLICTIN AHMAD TOHARI’S DI KAKI BUKIT CIBALAK - Tirmidi, Tirmidi; Putri, Faradila Arsylia; Khomariyah, Yanti; Indriyani, Kholifatul (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Since the proclamation of its independence until today, Indonesia has experienced civil conflicts. There are hundreds of civil conflicts that have the potential to become civil wars with very painful impacts. By taking lessons from the novel, it is hoped that the root of the problem that triggers conflict can be eliminated, and through the novel we can also learn the lesson that arbitrariness will definitely be met with resistance. Through a discourse analysis using an inter-textual analysis approach, this research is intended to reveal how a civil conflict occurs, in this case the conflict in the novel